History of Austria’s membership of the European Union (Economic and Political Thought, 2019)
The analysis presented in the article aims to determine the place androle of the Republic of Austria in the European Union. It shows the beginningof this country’s membership of the EU and the political crisis of theearly 2000 after the formation of the ÖVP and FPÖ coalition at the federalgovernment level, which was reflected in the imposition of political sanctionsby the other EU states. The analysis covers Vienna’s stand on the prospectsof the EU enlargement over the period of the last two decades. The articlealso presents the situation of this state against the background of the CommonForeign and Security Policy (CFSP), the relationship with NATO anda discussion on the so-called “Öxit”, i.e. the prospect of Austria’s withdrawalfrom the European Union. The article also shows Austrian society’s attitudetowards selected aspects of the European integration as well as the influenceof contemporary crises in the EU on the domestic and international situationof this Mid-European state.
Keywords: European policy of the Republic of Austria, European integration, migration crisis, Öxit, CFSP